PREVENTIVE EFFECT OF JASMINE FLOWER ETHANOL EXTRACT ON MSG- HIGH FAT DIET INDUCED IN MALE WISTAR RATS - Christoper, Wilson
Obesity is a high risk factor which contributes in many health problems in the world. About 3.4 billion people around the world dead because of obesity related diseases (diabetes, heart failure, cancer, etc.) According to Riset Kesehatan Dasar (Riskesdas) in 2013, prevalence of obesity in each province in Indonesia is 15.4%, in which whose overweight approximately 13.3% (BMI=27 is categorized as obesity). The flower of Jasminum sambac (L.) Ait. is known in Indonesia as the bridal ornament and fragrances. Besides, Jasminum sambac (L.), has antilipidemic, antioxidant and antimicrobial effect. Its capability for metabolizing lipid is potential as the treatment for preventing obesity. The objective of this research is to know the activity of Jasminum sambac (L.) Ait to prevent obesity in male Wistar rats which was induced by MSG-high fat diet method and the mechanism to prevent obesity. Antiobesity effect was evaluated by in vivo method, using male Wistar rats which was induced by MSG (2mg/kg weight) subcutaneously in 5 consecutive days. The induction was conducted together with high fat diet for 21 days. All animal was picked randomly and divided into 5 groups. The groups consisted of normal group, control group, jasmine flower group with dose of 100 mg/kg bw , jasmine flower group with dose of 200 mg/kg bw and the orlistat group with dose of 21.67 mg/kg bw. All group except the normal group was induced by MSG-high fat diet food for 21 consecutive days. Afterwards, ethanol extract of jasmine flowers (100 mg/kg weight and 200 mg/kg weight) was given as preventive treatment for the next 21 days, together with high-fat diet food. There were several parameters used to evaluate the efficacy of jasmine extract, including weight gaining, urin index, feses index, liver index and its histopathology, fat index, food index and the tryglyceride level measurement at the end of experiment. All parameter in each group was compared to the control group, and both of test group was compared to orlistat group. The ethanol extract of Jasminum sambac (L.) Ait. flower with the dose of 200 mg/kg bw showed significant difference on urin index 4.86%(Control = 2.45%), total fat index 1.85%(Control = 4.25%),, tryglyceride level 127.5 mg/dl(Control = 280.16 mg/dl), faeces index 2.98%(Control = 2.5%), and weight gaining rates was slower than the control group and was not significantly different compare to orlistat group. The ethanol extract of jasmine flower with dose of 200 mg/kg bw most likely effective in preventing obesity by preventing lipid absorption, besides possessing diuretic effect and may suppressing appetite.